Resources
Testimonials
Plans
Sign in
Sign up
Resources
Testimonials
Plans
AI tutor
Welcome to Bytelearn!
Let’s check out your problem:
(
8
x
2
)
2
3
=
\left(8 x^{2}\right)^{\frac{2}{3}}=
(
8
x
2
)
3
2
=
View step-by-step help
Home
Math Problems
Grade 7
Powers with negative bases
Full solution
Q.
(
8
x
2
)
2
3
=
\left(8 x^{2}\right)^{\frac{2}{3}}=
(
8
x
2
)
3
2
=
Apply Power Rule:
Evaluate the expression using the power of a power rule, which states that
(
a
m
)
n
=
a
m
∗
n
(a^m)^n = a^{m*n}
(
a
m
)
n
=
a
m
∗
n
.
(
8
x
2
)
2
3
=
8
2
3
×
(
x
2
)
2
3
(8x^{2})^{\frac{2}{3}} = 8^{\frac{2}{3}} \times (x^{2})^{\frac{2}{3}}
(
8
x
2
)
3
2
=
8
3
2
×
(
x
2
)
3
2
Simplify
8
2
3
8^{\frac{2}{3}}
8
3
2
:
Simplify
8
2
3
8^{\frac{2}{3}}
8
3
2
. Since
8
8
8
is
2
3
2^3
2
3
, we can rewrite
8
8
8
as
2
3
2^3
2
3
and then apply the power of a power rule.
\newline
8
2
3
=
(
2
3
)
2
3
=
2
3
∗
2
3
=
2
2
=
4
8^{\frac{2}{3}} = (2^3)^{\frac{2}{3}} = 2^{3*\frac{2}{3}} = 2^2 = 4
8
3
2
=
(
2
3
)
3
2
=
2
3
∗
3
2
=
2
2
=
4
Simplify
(
x
2
)
2
3
(x^{2})^{\frac{2}{3}}
(
x
2
)
3
2
:
Simplify
(
x
2
)
2
3
(x^{2})^{\frac{2}{3}}
(
x
2
)
3
2
. Using the power of a power rule again, we multiply the exponents.
(
x
2
)
2
3
=
x
2
∗
2
3
=
x
4
3
(x^{2})^{\frac{2}{3}} = x^{2*\frac{2}{3}} = x^{\frac{4}{3}}
(
x
2
)
3
2
=
x
2
∗
3
2
=
x
3
4
Combine Terms:
Combine the simplified terms to get the final answer.
4
×
x
4
3
4 \times x^{\frac{4}{3}}
4
×
x
3
4
More problems from Powers with negative bases
Question
Write the expression using an exponent.
\newline
2
×
2
2 \times 2
2
×
2
\newline
______
Get tutor help
Posted 1 year ago
Question
Evaluate the expression.
4
−
4
2
4 - 4^2
4
−
4
2
____
Get tutor help
Posted 1 year ago
Question
x
2
=
4
x^2 = 4
x
2
=
4
Get tutor help
Posted 1 year ago
Question
x
2
=
9
x^2 = 9
x
2
=
9
Get tutor help
Posted 1 year ago
Question
Solve for x.
\newline
x
2
=
0
x^2 = 0
x
2
=
0
\newline
Write your answer in simplified, rationalized form.
\newline
x
=
x =
x
=
_____ or
x
=
x =
x
=
_____
Get tutor help
Posted 1 year ago
Question
Solve for
x
x
x
.
\newline
8
=
2
x
8 = 2^x
8
=
2
x
\newline
x
=
x =
x
=
_____
Get tutor help
Posted 1 year ago
Question
Solve for
x
x
x
.
\newline
6
=
7
x
6 = 7^x
6
=
7
x
\newline
x
=
x =
x
=
_____
Get tutor help
Posted 1 year ago
Question
Select the equivalent expression.
\newline
(
(
8
−
5
)
/
(
2
−
2
)
)
−
4
=
?
((8^{-5})/(2^{-2}))^{-4}=?
((
8
−
5
)
/
(
2
−
2
)
)
−
4
=
?
\newline
Choose
1
1
1
answer:
\newline
(A)
\newline
(
8
20
)
/
(
2
8
)
(8^{20})/(2^{8})
(
8
20
)
/
(
2
8
)
\newline
(B)
\newline
(
2
6
)
/
(
8
9
)
(2^{6})/(8^{9})
(
2
6
)
/
(
8
9
)
\newline
(C)
\newline
(
1
)
/
(
8
⋅
2
2
)
(1)/(8\cdot 2^{2})
(
1
)
/
(
8
⋅
2
2
)
Get tutor help
Posted 11 months ago
Question
Select the equivalent expression.
\newline
(
b
7
4
5
)
−
3
=
?
\left(\frac{b^{7}}{4^{5}}\right)^{-3}=\,?
(
4
5
b
7
)
−
3
=
?
\newline
Choose
1
1
1
answer:
\newline
(A)
b
21
4
15
\frac{b^{21}}{4^{15}}
4
15
b
21
\newline
(B)
4
15
b
21
\frac{4^{15}}{b^{21}}
b
21
4
15
\newline
(C)
b
−
21
⋅
4
−
15
b^{-21}\cdot 4^{-15}
b
−
21
⋅
4
−
15
Get tutor help
Posted 1 year ago
Question
Select the equivalent expression.
\newline
(
3
3
⋅
6
6
)
−
3
=
(3^{3}\cdot6^{6})^{-3}=
(
3
3
⋅
6
6
)
−
3
=
?
\newline
Choose
1
1
1
answer:
\newline
(A)
1
3
9
⋅
6
18
\frac{1}{3^{9}\cdot6^{18}}
3
9
⋅
6
18
1
\newline
(B)
6
18
3
9
\frac{6^{18}}{3^{9}}
3
9
6
18
\newline
(C)
3
9
6
18
\frac{3^{9}}{6^{18}}
6
18
3
9
Get tutor help
Posted 1 year ago
Related topics
Algebra - Order of Operations
Algebra - Distributive Property
`X` and `Y` Axes
Geometry - Scalene Triangle
Common Multiple
Geometry - Quadrant